Trends in contingency in higher education, 2012-2016 - Schulman, Steven, author (Colorado State University. Libraries, 2019)
This report shows instructional staff employment -- tenured faculty, tenure track faculty, part-time non-tenure track faculty, full-time non-tenure track faculty, non-faculty instructors and graduate teaching assistants -- at every college and university in the U.S., as well as summary tables and charts. They include two measures of contingency, the percent of faculty off the tenure track (the "faculty non-tenure track rate") and the percent of instructional staff off the tenure track (the "contingency rate"). The measures of contingency presented in this report are taken from the CSAL Instructional Staff Employment reports from 2012 to 2016.
Keywords: academic employment; instructional staff; faculty; higher education